The diversities of feminine art and the pop cultures in the Islamic world - M. Al-Abbas Mohammed Baker, (Universiti Pendidikan Sultan Idris, 2016)
The diversities of feminine art and the pop cultures in the Islamic world by M. Al-Abbas Mohammed Baker,